Significance of electronic records in higher learning institutions - Ahmad, Rohayu; Abd Rahman, Nor Diana; A.Jamil@Kamarudzzaman, Azura; Mat Kamal, Siti Nuur-Ila (Universiti Teknologi MARA, Johor, 2025)
Electronic records are a crucial part of how higher learning institutions manage their information. They include electronic copies of academic, administrative, and research-related data that have been made, saved, and kept electronically. The integration of electronic record management systems (ERMS) has completely changed how higher learning institution work by making departmental service delivery, efficiency, and transparency better. Electronic records management systems (ERMS) have changed higher learning institutions for the better by making them more efficient, open, and able to provide better service in all areas of academics, administration, and research.